2021
DOI: 10.3390/plants10050925
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foliar and Ground-Applied Essential Nutrients on Huanglongbing-Affected Mature Citrus Trees

Abstract: The fate of foliar and ground-applied essential nutrients is the least studied topic under citrus greening or Huanglongbing (HLB)-affected citrus, which is inherently suffering from severe root decline because of HLB-associated problems. The objective of this study was to evaluate if ground-applied coupled with foliar spray of essential nutrients can reverse the decline in tree growth and understand the fate of the nutrients in the soil-root-tree interfaces. The treatments were arranged in a split-split plot d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Many studies have evidenced that plants can take up nutrients via their foliage. 36 Therefore, foliar uptake of Se and Si is regarded as the main mechanism for the regulation of Cd translocation and transport in rice plants. In this study, Se concentrations were also significantly increased in brown rice by foliar Se application (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have evidenced that plants can take up nutrients via their foliage. 36 Therefore, foliar uptake of Se and Si is regarded as the main mechanism for the regulation of Cd translocation and transport in rice plants. In this study, Se concentrations were also significantly increased in brown rice by foliar Se application (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this study is that Cd concentrations in all of the nodes, internodes, and leaves of rice were considered to explain the resistance to uptake of Cd by rice plants. Many studies have evidenced that plants can take up nutrients via their foliage . Therefore, foliar uptake of Se and Si is regarded as the main mechanism for the regulation of Cd translocation and transport in rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Uthman et al (2020), it was suggested that for up to 224 kg N ha -1 supply, the leaf N concentration, canopy volume and yield of HLB-affected trees increased whereas beyond that level no additional advantage was obtained. Atta et al (2021) also found out that split ground application of 224 kgha -1 of N and both foliar applied coupled with ground-applied Mn and Zn each at 9 kgha -1 sustainably supplied these nutrients within optimum ranges and further improved vegetative growth of HLB-affected trees. Foliar sprays are widely used but more expensive than soil-applied fertilizers and are more affected by regular rainfall, high temperatures, and heavy wind (Phuyal et al, 2020).…”
Section: Irrigation Nutrition Management and Hormonesmentioning
confidence: 87%
“…The complexity of nutrient management studies lies in their combination with declining fine root length density (FRLD) of HLB-affected citrus trees associated with HLB disease. Inherently, Florida sandy soils, with a high amount of rainfall or irrigation, and the transformation, leaching, and movement of the applied essential nutrients in the soil decreases nutrient uptake efficiency [6][7][8]. Therefore, the estimation of crop water demand based on reference crop evapotranspiration (ETo) and crop coefficient (Kc) are essential methodologies for improving crop water and nutrient uptake, hence productivity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ground-applied fertilizers are prone to unfavorable soil reactions that may result in the precipitation of nutrients to plant unavailable forms, leaching beyond the root zone, and runoff [6,10,11]. Meanwhile, following the infection of citrus trees with CLas, FRLD decline, water and nutrient uptake, xylem sap flow, and phloem movement are being severely disrupted [12,13].…”
Section: Introductionmentioning
confidence: 99%